Analysis of tumor microenvironment composition in vestibular schwannomas: insights into NF2-associated and sporadic variations and their clinical correlations - Nickl, Vera; Ziebolz, David; Rumpel, Charlotte; Klein, Dennis; Nickl, Robert; Rampeltshammer, Eva; Monoranu, Camelia M.; Ernestus, Ralf-Ingo; Matthies, Cordula; Löhr, Mario; Hagemann, Carsten; Breun, Maria (Frontiers in Oncology, 2024)
Objective: Vestibular schwannomas (VS), benign tumors stemming from the eighth cranial nerve's Schwann cells, are associated with Merlin gene mutations, inflammation, and the tumor microenvironment (TME), influencing tumor initiation, maintenance, and potential neural dysfunction. Understanding TME composition holds promise for systemic therapeutic interventions, particularly for NF2-related schwannomatosis. Methodology: A retrospective analysis of paraffin-embedded tissue from 40 patients (2013-2020), evenly divided by neurofibromatosis type 2 status, with further stratification based on magnetic resonance imaging (MRI) progression and hearing function. Immunohistochemistry assessed TME components, including T-cell markers (CD4, CD8, CD25), NK cells (CD7), and macrophages (CD14, CD68, CD163, CCR2). Fiji software facilitated image analysis.Results: T-cell markers (CD4, CD8, CD7) exhibited low expression in VS, with no significant NF2associated vs. sporadic distinctions. Macrophage-related markers (CD14, CD68, CD163, CCR2) showed significantly higher expression (CD14: p = 0.0187, CD68: p < 0.0001, CD163: p = 0.0006, CCR2: p < 0.0001). CCR2 and CD163 significantly differed between NF2associated and sporadic VS. iNOS, an M1-macrophage marker, was downregulated. CD25, a regulatory T-cell marker, correlated significantly with tumor growth dynamics (p = 0.016).Discussion: Immune cells, notably monocytes and macrophages, crucially contribute to VS pathogenesis in both NF2-associated and sporadic cases. Significant differences in CCR2 and CD163 expression suggest distinct immune responses. Regulatory T-cells may serve as growth dynamic markers. These findings highlight immune cells as potential biomarkers and therapeutic targets for managing VS.